PEMANFAATAN SERBUK GERGAJI SEBAGAI SUBSTITUSI BAHAN BAKAR PADA PROSES PEMBAKARAN - KILN DI PABRIK SEMEN DENGAN PENDEKATAN LIFE CYCLE ASSESMENT (LCA) - Ahmad Zaky Nugraha; Edi Iswanto Wiloso; Mohammad Yani (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2018)
Cement production was a process that requires huge thermal energy and produces high greenhouse gas emissions. Co-processing or utilising alternative materials and alternative fuels for the combustion process in kiln was a solution to meet energy needs and reduce greenhouse gas emissions in the cement industry. This study aimed to analyze input, output, environmental impacts of cement production and calculate CO2-eq reduction from the system used alternative fuels on co-processing. The method used to determine differences and calculate CO2-eq reduction due to co-processing was life cycle assessment (LCA) and system approach. Based on the results of the LCA, the case 1 that used 100% coal energy required 3.50 GJ/ton-cement, 126 kWh/ton-cement, 2.19 L-diesel-oil/ton of cement and emited 0.84 ton-CO2-eq/ton-cement. Case 2 that had been substituted alternative fuels (saw dust) required 3.03 GJ per ton of cement, 118 kWh per ton of cement, 1.44 L diesel oil per ton of cement and emited 0.92 ton-CO2-eq per ton of cement. The results of global warming impact of  case 2 was higher than case 1. The assumption of  climate neutral made reduction global warming impact of case 2 by 14.65% and decrease CO2 emissions annually in plant by 71,601 tons CO2/year.  This result show that utilization of saw dust as biomass of climate neutral can be applied as an input for overall company specific emissions calculation to meet government regulation.